Українські балади в Канаді: пристосування до нового життя в новій країні - Кононенко, Н. (Народна творчість та етнологія, 2012)
Natalie Kononenko. Ukrainian Ballads in Canada: Adjusting to New Life in a New Land. Folk ballads give voice to those who could not compose narratives on their own. Ballads are an excellent key to the emotional life of immigrant groups. How did oral texts deal with the Ukrainian Pioneer experience? Ukrainian Canadian ballads are different from their Ukrainian variants. The comparative investigation gave a possibility to get away from stereotypes and to examine immigrant assimilation in a nuanced way that draws our attention to the words of the immigrants themselves.